Production Performance Of Commercial Laying Hens At The Tiga Putri Business Group In Bambaea Village, East Poleang District, Bombana Regency - Nur Afni; Hajar Hajar; Inal Inal; Awal Maulid Sari; Wa Ode Umrawati Latif; Farra Sasmita (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2026)
This study aimed to evaluate the production performance of commercial laying hens at Kelompok Usaha Tiga Putri using key indicators, including feed consumption, Feed Conversion Ratio (FCR), Hen Day Production (HDP), egg weight, and mortality rate. A quantitative descriptive case study design was employed. Data were collected through direct observation, interviews, and production recording over a 30-day period involving 60 laying hens. The results indicate that feed consumption was relatively stable, with a total intake of 208,630 g and minimal feed residue, reflecting efficient feeding management. The average FCR value was 2.2, indicating good feed utilization efficiency. The average HDP reached 88%, categorized as high and within commercial production standards. Egg weight remained consistent at 59–60 g/egg, classified as medium to large size. The mortality rate was low at 2%, indicating favorable flock health conditions. Overall, the production system demonstrated good management efficiency in supporting laying hen productivity. However, improvement is still required in feed formulation, ration quality optimization, and housing environmental control to further enhance production efficiency and sustainability. The findings provide practical insights for improving laying hen management in small to medium-scale commercial poultry farms.